2019
DOI: 10.1155/2019/1314623
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Insufficiency, Abdominal Sepsis, and Patients’ Age Are Associated with Decreased Paraoxonase-1 (PON1) Activity in Critically Ill Patients with Multiple Organ Dysfunction Syndrome (MODS)

Abstract: Oxidative stress and uncontrolled inflammation are hallmarks of sepsis, leading to organ failure and death. As demonstrated in animal studies, oxidative stress can be alleviated by antioxidant therapies. Paraoxonase-1 (PON1) is a serum-based antioxidant, anti-inflammatory agent, detoxifier, and quorum-sensing factor found to be a prognostic marker in sepsis. However, its associations with multiple organ dysfunction syndrome (MODS), a complication of sepsis and the leading cause of death in the surgical intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In a small study including ten patients in-and outside the ICU, septic patients had reduced CEC, but the activity of PON1 was not significantly different (16). A recent report showed that activity of PON1 was a good marker for the development of multiorgan dysfunction syndrome (46). Novak et al (47) showed a non-significant trend of lower AEA in non-survivors of sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…In a small study including ten patients in-and outside the ICU, septic patients had reduced CEC, but the activity of PON1 was not significantly different (16). A recent report showed that activity of PON1 was a good marker for the development of multiorgan dysfunction syndrome (46). Novak et al (47) showed a non-significant trend of lower AEA in non-survivors of sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…It was also observed that decreased PON1 activity was related to the increased occurrence of atherogenic dyslipidemia [ 30 ]. Bednarz-Misa et al noted a significantly decreased PON1 level among patients that were admitted to the intensive care unit with multiple organ disfunction syndrome (MODS) and reported that lower PON1 activity was associated with cardiovascular insufficiency [ 31 ]. Moreover, Bednarz-Misa et al suggested that PON1 could be used as a marker of cardiovascular insufficiency with an accuracy of 82% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that PON1 exhibits activity of arylesterase (ARE) (aromatic carboxylic acid esters hydrolysis), lactonase (lactones hydrolysis), and paraoxonase (organophosphatase hydrolysis) [15][16][17] . These activities are described as one of PON1 physiological functions as well as the antioxidant activity which is considered another biological role of PON1 [18,19] . It was also demonstrated that more than 95% of the PON1 in serum exhibits ARE activity (ARE-PON1) as in vitro investigated by controlling phenylacetate hydrolysis [16] .…”
Section: ©Annals Of Tropical Medicine and Public Health S243mentioning
confidence: 99%